A history of affirmative action, 1619-2000 - Rubio, Philip F. (Book collections on Project MUSE., 2001)
What is it about affirmative action that makes this public policy one of the most contentious political issues in the United States today?. The answer to this question cannot be found by studying the recent past or current events. To understand the current debate over affirmative action, we must grapple with all of America's racial history, from colonial times, through slavery, Reconstruction, the Jim Crow era, the Civil Rights era, to the present day. Philip Rubio argues that misunderstanding the history of affirmative action is the principal reason that most white people have difficulty in s.